KONFLIK PERAN, KETIDAKJELASAN PERAN, DAN KELEBIHAN PERAN TERHADAP KINERJA AUDITOR DENGAN TEKANAN WAKTU SEBAGAI PEMODERASI - Eka Ratna Sari, Ni Putu; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2016)
Auditor performance is a primary judgement by client, users of audit services, and public. This study was conducted to determine the influence of role conflict, role ambiguity, and role overload on auditor performance with  time pressure as a moderating variable. Sampling method used is non-probability sampling method with purposive sampling technique so eventually obtained samples totaling 46 samples. Data is collected by interview and questionnaire methods which is sending questionnaires to the auditors in  public accounting firm in Bali. Data analysis technique used to test the hypothesis is Moderated Regression Analysis (MRA). Based on the hypothesis testing results show that role conflict, role ambiguity, and role overload negatively affect to auditor performance. The results also showed that time pressure can moderate the influence of role conflict and role overload on auditor perfomance, but can not moderate the effect of role ambiguity on auditor performance.
Keywords: auditor performance, role conflict, role ambiguity, role overload, and time pressure